Three-dimensional (3D)-printed custom-made titanium ribs for chest wall reconstruction post-desmoid fibromatosis resection - Chen Yang; Lei Chen; Xiangyu Xie; Changping Wu; Qianyun Wang (Computer Assisted Surgery)
Desmoid fibromatosis (DF) is a rare low-grade benign myofibroblastic neoplasm that originates from fascia and muscle striae. For giant chest wall DF, surgical resection offer a radical form of treatment and the causing defects usually need repair and reconstruction, which can restore the structural integrity and rigidity of the thoracic cage. The past decade witnessed rapid advances in the application of various prosthetic material in thoracic surgery. However, three-dimensional (3D)-printed custom-made titanium ribs have never been reported for chest wall reconstruction post-DF resection. Here, we report a successful implantation of individualized 3D–printed titanium ribs to repair the chest wall defect in a patient with DF.